Assessment of Quality of Life and Behavioral Problems in Children with Central Precocious Puberty - Shaymaa Raafat; Esraa Abdelaal; Ihsan Mowafi; Mona Khalil (Oman Medical Journal)
Objectives: We sought to estimate the impact of central precocious puberty (CPP) on psychosocial aspects in the cohort of children and to assess whether these aspects changed after treatment with gonadotropin-releasing hormone (GnRH) analogues. Methods: A case-control study enrolled 30 CPP children and 30 normal controls. The CPP group was assessed with emphasis on anthropometric measurements (Tanner staging for pubertal changes). The hormonal profile included gonadotropins, estradiol or testosterone, and GnRH stimulation test. The instruments used for neuropsychological assessment included the Arabic version of the pediatric quality of life inventory TM 4.0, the Child Behavior Checklist (CBCL), and IQ testing. Results: The mean study group age was 5.1 ± 2.3 years compared to 5.2 ± 2.2 years in the control group; 29 patients and 29 controls (96.7%) were females. CPP children had significantly lower scores than controls in health-related quality of life (QoL) domains except school functioning without significant changes in CBCL scores and cognitive function. There was a statistically significant improvement in these scores after they were treated with GnRH analogues for a year. Conclusions: There are significant aberrations in CPP children’s QoL with no effect on behavior or cognition. After treatment with GnRH analogues for a year, QoL and CBCL T-scores showed a significant improvement.